2017
DOI: 10.3791/55107
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Neutrophil Phagosome and Cytoplasm Using a Ratiometric pH Indicator

Abstract: Neutrophils are crucial to host innate defense and, consequently, constitute an important area of medical research. The phagosome, the intracellular compartment where the killing and digestion of engulfed particles take place, is the main arena for neutrophil pathogen killing that requires tight regulation. Phagosomal pH is one aspect that is carefully controlled, in turn regulating antimicrobial protease activity. Many fluorescent pH-sensitive dyes have been used to visualize the phagosomal environment. S-1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…An acidic environment in phagosomes directly aids in bacterial killing and is also important for the activation of pH-sensitive antimicrobial enzymes ( Sedlyarov et al, 2018 ; Flannagan et al, 2015 ). To determine if the HBC phagosome becomes acidic during maturation, we profiled the uptake of zymosan particles tagged with a pH-sensitive probe (Carboxy SNARF-1 [S-1]; Foote et al, 2017 , 2019 ). After allowing phagocytosis for 20 min, we find that the HBC phagosome becomes rapidly acidic, reaching a pH of ∼4.5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An acidic environment in phagosomes directly aids in bacterial killing and is also important for the activation of pH-sensitive antimicrobial enzymes ( Sedlyarov et al, 2018 ; Flannagan et al, 2015 ). To determine if the HBC phagosome becomes acidic during maturation, we profiled the uptake of zymosan particles tagged with a pH-sensitive probe (Carboxy SNARF-1 [S-1]; Foote et al, 2017 , 2019 ). After allowing phagocytosis for 20 min, we find that the HBC phagosome becomes rapidly acidic, reaching a pH of ∼4.5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Placental macrophage phagosomal pH measurements were performed by adapting a method using the fluorescent-sensitive pH dye S-1 with a dual-emission spectrum ( Foote et al, 2017 ). Carboxy S-1-succinimidyl ester (Thermo Fisher Scientific) was coupled to zymosan coated beads (Thermo Fisher Scientific) and opsonized with human serum.…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed previous findings (13) that R19-S does not react with H 2 O 2 or with MPO in the absence of chloride, and observed that the fluorescence yield was similar when HOCl was added as a reagent or was generated by MPO, chloride, and an equivalent concentration of H 2 O 2 (not shown). It has recently been reported that a pH of 8.5-9 is achieved within neutrophil phagosomes (12). We therefore tested the reactivity of HOCl with R19-S at a higher pH.…”
Section: Reactivity Of R19-s With Other Hypohalous Acids and Haloaminesmentioning
confidence: 99%
“…Several studies involving analysis of phagosomal contents provide evidence that HOCl is produced (3, 6 -10) but there is debate about how much, whether this is sufficient to kill, and whether it does so directly. Others query whether HOCl is produced at all (11,12). To gain a greater understanding of how MPO functions during phagocytosis, real-time monitoring of HOCl at intracellular sites is needed.…”
mentioning
confidence: 99%
“…The following protocol is described in more detail elsewhere 27 . The wells were washed twice with BSS buffer to remove non-adherent cells, then buffer containing 1 μg/ μl carboxy SNARF-1, AM ester acetate (ThermoFisher) was added for 25 minutes to label the cytosol, and then washed off with BSS buffer.…”
Section: Phagosomal Ph Measurementsmentioning
confidence: 99%